Speech, Language, and Communication 1995
DOI: 10.1016/b978-012497770-9/50006-6
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Word Recognition and Production

Abstract: Most language behavior consists of speaking and listening. However, the recognition and production of spoken words have not always been central topics in psycholinguistic research. Considering the two fields together in one chapter reveals differences and similarities. Spokcn-word recognition studies began in earnest in the 1970s, prompted on one hand by the develop ment of laboratory tasks involving auditory presentation and on the other hand by the realization that the growing body of data on visual word rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…In this case, the Russian word sharik was a crosslinguistic COHORT of the English target word shark (cf. Marslen-Wilson, 1987; see also Cutler, 1995), i.e., the beginning portion of the name of the target object bore phonological similarity to the name of one of the other objects in the other language. It was found that, when instructed to pick up an object whose name in language A was initially phonologically similar to the name of another object in language B, bilingual subjects frequently looked at the cross-linguistic cohort, even when the other language was not being used overtly (Spivey and Marian, 1999;Marian and Spivey, 2003).…”
mentioning
confidence: 99%
“…In this case, the Russian word sharik was a crosslinguistic COHORT of the English target word shark (cf. Marslen-Wilson, 1987; see also Cutler, 1995), i.e., the beginning portion of the name of the target object bore phonological similarity to the name of one of the other objects in the other language. It was found that, when instructed to pick up an object whose name in language A was initially phonologically similar to the name of another object in language B, bilingual subjects frequently looked at the cross-linguistic cohort, even when the other language was not being used overtly (Spivey and Marian, 1999;Marian and Spivey, 2003).…”
mentioning
confidence: 99%
“…This transition is smooth and long enough to produce the acoustic trace of a phone between the two vowels-an "intrusive" glide (as in Malay; Browman and Goldstein, 1990;Gick, 2003). The timing options in Figure 1 are attributed to the general competition between signal compression and signal recovery, or ease of articulation and ease of perception (e.g., Hunnicutt, 1985;Cutler, 1987;Lindblom, 1996;Kirchner, 1998). The distinction between representations involving overlapping rectangles and representations involving circles stands for the distinction between phonetic realizations and underlying phonological forms.…”
Section: Minimal Epenthesismentioning
confidence: 99%
“…In summary, whereas evidence for the BOSS effect is fairly weak in the reading of English, there is certainly no evidence that the phonologically defined syllable is involved in the recognition of visually presented words. This is hardly surprising, however, given that English speakers lack sensitivity to syllable structure even in spoken word processing (e.g., Cutler, 1995;Cutler et al, 1986). On the other hand, French has relatively clear syllable boundaries, and French speakers are sensitive to this fact (e.g., Cutler, 1995;Cutler & Norris, 1988;Dupoux, 1993;Mehler, 1981), which means that the phonological syllable has a greater potential to be involved in visual word recognition for French than for English.…”
Section: Visual Processing Of Syllabic Structure In Englishmentioning
confidence: 99%
“…The answer to such a question could be different from one language to another, especially because the lexical access unit used for spoken word recognition has been shown to be different in different languages. For example, it appears that the syllable plays an important role in the perception, segmentation, and comprehension of spoken French (Cutler, 1995;Cutler & Norris, 1988;Dupoux, 1993;Mehler, 1981), but not so obviously in spoken English (e.g., Bradley, Sánchez-Casas, & García-Albea, 1993;Cutler, 1995;Cutler, Mehler, Norris, & Segui, 1986). This is presumably due to the fact that the phonological system of these two languages is different.…”
mentioning
confidence: 99%
See 1 more Smart Citation